Summer annual forages in south central Kansas - Heer, William F.; Blasi, Dale A.; Fjell, Dale L. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Six summer annuals and three forage sorghums were evaluated for forage yield and quality under south central Kansas dryland conditions. When cut in the late boot to early heading stage, all forage types (millet, sudan, sorghum-sudan, and forage sorghum) produced similar dry matter yields, with no consistent differences in nutritional quality. Allowing the forages to reach maturity prior to cutting increased total yield per acre but decreased the crude protein content. The millets were higher in protein at maturity than the sudans or forage sorghums. However, the forage sorghums produced the most mature forage, whereas common sudan yielded the least. Cool, moist conditions during the growing season allowed the forages to develop slowly.
Keywords: Beef; Summer annuals; Forage sorghum; Yield; Forage quality; Nitrate